2020
DOI: 10.3389/fbioe.2020.581619
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Activation Patterns Are More Constrained and Regular in Treadmill Than in Overground Human Locomotion

Abstract: The use of motorized treadmills as convenient tools for the study of locomotion has been in vogue for many decades. However, despite the widespread presence of these devices in many scientific and clinical environments, a full consensus on their validity to faithfully substitute free overground locomotion is still missing. Specifically, little information is available on whether and how the neural control of movement is affected when humans walk and run on a treadmill as compared to overground. Here, we made u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 70 publications
(148 reference statements)
6
21
0
Order By: Relevance
“…We focused the analysis on all 15 muscles recorded from the lower limb, trunk, and upper limb, but also carried out an analysis on a subset of these muscles in order to confirm the findings from the literature where the main focus is often on the lower limb muscles (Supplementary Material 1). We found that the number of synergies across groups were much lower and comparable to what has previously been found in walking in children and adults (e.g., Dominici et al, 2011;Oliveira et al, 2016;Hinnekens et al, 2020;Mileti et al, 2020;Sylos-Labini et al, 2020) where four synergies is one of the most common findings. The activation patterns and the weighting coefficients were also comparable to what has previously been found in literature.…”
Section: Structure Of Muscle Synergiessupporting
confidence: 87%
“…We focused the analysis on all 15 muscles recorded from the lower limb, trunk, and upper limb, but also carried out an analysis on a subset of these muscles in order to confirm the findings from the literature where the main focus is often on the lower limb muscles (Supplementary Material 1). We found that the number of synergies across groups were much lower and comparable to what has previously been found in walking in children and adults (e.g., Dominici et al, 2011;Oliveira et al, 2016;Hinnekens et al, 2020;Mileti et al, 2020;Sylos-Labini et al, 2020) where four synergies is one of the most common findings. The activation patterns and the weighting coefficients were also comparable to what has previously been found in literature.…”
Section: Structure Of Muscle Synergiessupporting
confidence: 87%
“…This is also confirmed by the addition of a new synergy if an extra voluntary movement, such as kicking, is included in the walking ( Ivanenko et al, 2005 ). Previous studies also demonstrated that treadmill locomotion shares similar muscle synergy structures with overground locomotion ( Oliveira et al, 2016 ; Mileti et al, 2020 ). Similarly, balance-specific muscle synergies were consistently recruited in different types of postural tasks ( Torres-Oviedo and Ting, 2010 ).…”
Section: Introductionmentioning
confidence: 73%
“…In the study, the muscle synergies were analyzed for treadmill walking. A previous study demonstrated that treadmill locomotion shares similar muscle synergy structures with overground locomotion (Oliveira et al, 2016;Mileti et al, 2020) although synergy activations were more consistent in the treadmill condition (Mileti et al, 2020). Since we classified group-specific synergies based on synergy structures, we assume that walking environment may rarely influence the results.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the current results were generated only during treadmill walking at a preferred and a fixed speed. There might be slightly differences between treadmill and overground walking; however, muscle synergies have been shown to be generally consistent for both environments (Oliveira et al, 2016 ; Mileti et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%